Evidence of the content validity of an app on the oral health of elderly people with diabetes mellitus. - Fonsêca, Maria Raquel Crispim Paschoal da; Paschoal Dantas, Cecília Maria; Oliveira Pereira, Jóison; Mourão Pinho, Roberto Carlos; Pinheiro Costa e. Silva, Susanne; Laureano Dalle Piagge, Carmem Silvia; Batista Mélo, Cláudia (Rev Rene, 2025)
Objective: to verify the evidence of content validity of the app with the theme of oral health and diabetes mellitus in the elderly. Methods: technological development study of an app, based on Systemic Instructional Design and implemented using the React Native framework, using the JavaScript programming language and the React library. It was va lidated by 19 expert judges and then evaluated by 19 elderly people. The criterion for content validation agreement was 95%, as analyzed using the Content Validation Index, and suggested adjustments were made accordingly. Results: a Content Validation Index was obtained, with averages of 0.94 by the expert judges, 0.98 by the older participants, and 0.95 overall for the assessed items, indicating that it was recognized as relevant and accessible. Conclusion: the application was developed, and, according to experts and the elderly, it demonstrates evidence of content validity, with high scores obtained for this measure, fully confirming its applicability and relevance. Contributions to practice: the use of mobile applications as a tool for educating the elderly about oral health can encourage greater self-care and awareness of its importance in the management and control of diabetes mellitus.